Design and analysis of motion and energy regulating vibration harvester. (February 2022) - Satpute, Nitin; Jugulkar, Lalitkumar; Jabade, Siddharth; Korwar, Ganesh; Arawade, Swapnil
In this paper a novel design of energy harvester has been proposed, which converts harmonic or random vibrations energy into useful electric power. The energy harvester comprises of mechanical motion rectifier, motion regulator, strain energy storage element and a rotary electric generator. The mechanical motion rectifier comprises of a spatial mechanism with unidirectional bearings and spherical joint that converts the linear oscillating force into unidirectional torque pulses. Further, motion regulating mechanism directs the energy flow to the strain energy storage element and drives the electric generator. The arrangement ensures that flow of vibration energy is regulated such that it is stored in the spring up to a threshold limit and thereafter dissipated to the electric generator. Rigid body simulations in Adams and Matlab have been used in design and analysis of the energy harvester with investigations for the effect of significant design parameters. Experimentation on a prototype has been performed to validate the numerical model which delivered 4.13 W of peak power and average power of 0.12–0.52 W within frequency range of 1–15 Hz. Simulation results on a real size device with higher torsion spring stiffness indicates that the harvester can operate with 69.8% efficiency and deliver 0.32–2.45 W of average power for frequency of 0.5–4 Hz.